Rusty-Pipe Syndrome: case report - Carrasco, Amparo (2016)
Bilateral thelorrhagia or bloody discharge from the nipple is an alarm symptom, but it can be benign during pregnancy and breastfeeding. A careful differential diagnosis is required and surgical interventions should be avoided unless an underlying cause is discovered. This clinical condition is known as rusty-pipe syndrome. We report the case of a 30-year-old primiparous woman who presented with bilateral thelorrhagia after eutocic delivery at 40 weeks in the Dr. Peset Hospital, Valencia (Spain).